Aspects of an automatic system of implants of radioac-tive seeds and anatomic object simulator for tests in prostate brachytherapy. - Leonardo Santiago Melgaço Silva; Viviane Vitória Bento Braga; Tarcisio Passos Ribeiro Campos (Brazilian Journal of Radiation Sciences, 2019)
This work presents the development of an automatic radioactive seed implantation system (PSIS). PSIS may assist the testing permanent implants procedure in the prostate. These tests will be important in measurements of absorbed doses in the pelvic structures, involving the organs and tissues at risk to improve planning, seed positioning and dosimetry. The automated Prostate Seed Implant System (PSIS) has been designed to meet operational needs, which offers the freedom when positioning the brachytherapy needle inside the treatment area ensuring repeatability and fidelity to the planned treatment. Both the ultrasound probe and the seed implant needle are driven by stepper motors, ATMEGA microcontroller, bearings, aluminum shafts and a GUI (Graphical User Interface). Movement of both the probe and the needle holder was performed by fixed spindle on a threaded rod going through a stepper motors by a coupling. These engines were chosen due to the necessity of movements precision that these types of motors provide. The project was developed and the PSIS prototype was assembled. The prototype presented acceptable operating characteristics for prostate implants. The advantage of this system is that the automation of the application provides an accurate positioning and movement of both probe and seed application. In addition to this study, seeds implantation tests will be performed, and such tests will be essential in protocol validation processes.